Antithrombotic management and device-related bleeding complications in patients undergoing cardiac implantable electronic device implantations: A single-center study - Nithit Tianchetsada (2019)
© 2018, Medical Association of Thailand. All rights reserved. Background: Each year, 1.65 million people around the world are implanted with Cardiac Implantable Electronic Devices [CIEDs], and 14% to 35% of those patients are receiving oral anticoagulants [OACs] or antiplatelet therapy prior to the surgery. These drugs increased bleeding complications in CIED implantations. Currently, we have no data on device-related bleeding complications [DRBCs] among Thai patients receiving OACs and/or antiplatelet therapy prior to CIED implantation. Materials and Methods: We retrospectively reviewed consecutive patients who underwent CIED implantations and continued to follow-up at the Siriraj Device Clinic in 2016. The baseline characteristics, comorbidities, types of CIED, CIED indications, types of antithrombotic and DRBCs data were collected. Siriraj protocol requires that patients follow-up at the device clinic 12 to 16 days post implantation and be evaluated for DRBCs by two device-clinic staff. If DRBCs are detected, a caliper is used to measure the size in three dimensions. Our primary outcome is the incidence of DRBCs among patients who received antithrombotic drugs and the secondary outcome is the incidence of DRBCs for each group of antithrombotic drugs. This study was approved by the Institutional Review Board [IRB]. Results: Three hundred patients underwent CIEDs implantations then continued follow-up at the device clinic between January and December 2016; their mean age was 69.7±14.5 years, and 60.3% were male. The implanted CIEDs consisted of pacemakers (59.7%), automated implantable cardioverter defibrillators (AICDs, 28.3%) and cardiac resynchronization therapy device (CRTs, 12%). Antithrombotic used, found in 73% (218) of the implanted CIED patients, was distributed into the following groups, single-antiplatelet therapy (SAPT, 31%, 93), dual antiplatelet therapy (DAPT, 13%, 39), OAC plus antiplatelet (9.7%, 29), triple therapy (DAPT plus OAC, 1.3%, 4), warfarin (14.7%, 44) and non-vitamin K antagonist OAC (NOAC, 3%, 9). The primary outcome showed a DRBC incidence of 12.8% among patients using antithrombotics. Of those patients, the DRBCs detected 9.7% (9) of patients in the SAPT group, 15.4% (6) in the DAPT group, 13.8% (4) in the OAC-plus-antiplatelet group and 20.5% (9) in the warfarin group. No DRBCs were detected in either the no-antithrombotic group (82) or the NOAC group (9). However, almost all the DRBC patients resolved spontaneously without intervention. Unfortunately, one DRBCs patient who only took aspirin (81 mg) was admitted for a hematoma evacuation. The different in size of the CIED revealed a significant correlation in the incidence of DRBCs, as shown in the analysis, the CRTD-implanted patients had more DRBCs than the pacemaker-implanted patients (OR 4.36, 95% CI 1.61 to 11.8, p-value 0.004). Moreover, a multivariate analysis demonstrated an increased level of DRBCs among patients in the CAD and warfarin groups (OR 3.41, 95% CI 1.01 to 11.5, p-value 0.048) and (OR 2.96, 95% CI 1.17 to 7.46, p-value 0.022) respectively. Surprisingly, the level of DRBCs was decreased among patients who had used statins in the non-CAD group (OR 0.17, 95% CI 0.04 to 0.80, p-value 0.024). Conclusion: A comparison of CIED-implantation patients who had been using and had not been using antithrombotic drugs prior to surgery revealed that, although the incidence of DRBCs increased when antithrombotics were used, those DRBCs were still not clinically significant as they resolved spontaneously without the need for treatment. This finding supports the safety of continuing to use antithrombotic drugs on patients undergoing CIEDs implantations.